2017
DOI: 10.1016/j.visres.2017.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Müller cells and diabetic retinopathy

Abstract: Müller cells are one of the primary glial cell types found in the retina and play a significant role in maintaining retinal function and health. Since Müller cells are the only cell type to span the entire width of the retina and have contact to almost every cell type in the retina they are uniquely positioned to perform a wide variety of functions necessary to maintaining retinal homeostasis. In the healthy retina, Müller cells recycle neurotransmitters, prevent glutamate toxicity, redistribute ions by spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
200
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(210 citation statements)
references
References 116 publications
7
200
0
3
Order By: Relevance
“…Diabetes-induced retinal vascular damages have been extensively studied by several laboratories [75][76][77]. Activation of the Muller glia is shown to be closely related to neurovascular changes in the diabetic retina [59,[78][79][80]. However, since the focus of our present study is solely on diabetes-induced neurodegeneration in the retina, we have not evaluated these changes in response to SMOX inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes-induced retinal vascular damages have been extensively studied by several laboratories [75][76][77]. Activation of the Muller glia is shown to be closely related to neurovascular changes in the diabetic retina [59,[78][79][80]. However, since the focus of our present study is solely on diabetes-induced neurodegeneration in the retina, we have not evaluated these changes in response to SMOX inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Although MGCs are highly resistant cells, they can activate the caspase‐1 pathway, leading to pyroptosis, an infrequent cell death program. The Mohr group suggested that pyroptosis could be a mechanism to eliminate MGCs secreting IL‐1β, in order to decrease retinal inflammation (Coughlin, Feenstra, & Mohr, ).…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…Recent studies, however, have demonstrated that retinal neurodegeneration is a critical feature associated with the progression of the disease and that early retinal neuronal injury actually precedes microangiopathy (18)(19)(20)(21)(22)(23). Indeed, all retinal layers (ganglion, bipolar, amacrine, and photoreceptor cell), demonstrate altered functions (as assessed by electroretinography and central vision analysis under reduced contrast and luminance conditions) prior to observable micropathy lesions (as assessed by fundus photography) (24)(25)(26)(27)(28)(29). Therefore, defining diabetic retinopathy simply as a "microvascular complication of diabetes" is a misnomer and restricts our understanding of the condition as well as potential therapeutic approaches to address it.…”
Section: Introductionmentioning
confidence: 99%